Neoparamoeba spp. and their eukaryotic endosymbionts similar to Perkinsela amoebae (Hollande, 1980): coevolution demonstrated by SSU rRNA gene phylogenies - Dyková, Iva; Fiala, Ivan; Pecková, Hana (European journal of protistology, 2008)
The molecular phylogeny of Neoparamoeba spp. based on SSU rDNA was updated by including new sequences of strains isolated from an invertebrate and an alga. In total, 59 sequences of strains representating N. pemaquidensis, N. branchiphila, N. aestuarina and N. perurans were analysed. Sequences of SSU rDNA of eukaryotic endosymbionts (Perkinsela amoebae-like organisms) were prepared from 34 samples of genomic DNA of strain-representatives of N. pemaquidensis, N. branchiphila and N. aestuarina. Comparison of phylograms reconstructed from corresponding SSU rDNA sequences of host amoebae and their symbionts revealed a high level of congruence, which argues very strongly for coevolution of these two eukaryotic organisms.
Keywords: RNA, Protozoan; Animals; Phylogeny; RNA, Ribosomal; RNA ribozomální; symbióza; zvířata; sestřih RNA; fylogeneze; Symbiosis; RNA Splicing; RNA protozoální; Eukaryota